2022
DOI: 10.3390/jof8060571
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Enzymatic Activities of Oceanic Pelagic Fungal Strains and the Influence of Temperature

Abstract: Although terrestrial and aquatic fungi are well-known decomposers of organic matter, the role of marine fungi remains largely unknown. Recent studies based on omics suggest that marine fungi potentially play a major role in elemental cycles. However, there is very limited information on the diversity of extracellular enzymatic activities performed by pelagic fungi in the ocean and how these might be affected by community composition and/or critical environmental parameters such as temperature. In order to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 90 publications
1
20
0
Order By: Relevance
“…Spores, yeasts (in suspension) and fragmented mycelia in suspension or as an agar plug/block are inoculated into a liquid assay medium in flasks. For yeast species, optical density of subsamples is measured periodically at 660 nm, which reflects growth (Heitger & Baltar, 2023; Salazar Alekseyeva et al., 2022). Filamentous fungi do not produce homogenous growth in liquid media.…”
Section: Methods For Studying Planktonic Marine Fungimentioning
confidence: 99%
See 2 more Smart Citations
“…Spores, yeasts (in suspension) and fragmented mycelia in suspension or as an agar plug/block are inoculated into a liquid assay medium in flasks. For yeast species, optical density of subsamples is measured periodically at 660 nm, which reflects growth (Heitger & Baltar, 2023; Salazar Alekseyeva et al., 2022). Filamentous fungi do not produce homogenous growth in liquid media.…”
Section: Methods For Studying Planktonic Marine Fungimentioning
confidence: 99%
“…Another approach involves measuring the concentration of ergosterol as a proxy for fungal biomass (Gessner, 2020), with a focus on Ascomycota and Basidiomycota (Dikarya). The ergosterol extraction method was recently adapted to marine fungi to allow for the quantification of fungal biomass in the oligotrophic (low productive) regions (Salazar Alekseyeva et al., 2022). However, the ergosterol‐based method falls short when dealing with Chytridiomycota taxa (Gutiérrez et al., 2020), which is important to consider during phytoplankton blooms.…”
Section: Methods For Studying Planktonic Marine Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…For the enzymatic assays, sterile 96-well microplates with F bottom and low protein binding (XT64.1, Carl Roth Karlsruhe, Baden-Wurtemberg, Germany) were used. The protocol was based on Hoppe [45] and Salazar Alekseyeva, Herndl, and Baltar [67]. The MCA fluorophore was dissolved in 2-methoxyethanol to a final concentration of 100 µM, 50 µM, 10 µM, and 1 µM, whereas MUF was diluted to a final concentration of 2000 µM, 1000 µM, 100 µM, and 50 µM.…”
Section: Measuring Extracellular Enzymatic Activity and Fungal Biomas...mentioning
confidence: 99%
“…Several microorganisms, specially fungi, perform cellulolytic activities with three major classes of enzymes such as endoglucanases, exoglucanases, and β-glucosidases [72][73][74][75][76]. The hydrolysis of cellulose has been reported by a wide variety of marine fungi [67,75,[77][78][79][80][81][82][83][84], but their capability to decompose this complex compound depends on their enzymatic machinery [85]. Vaz, Rosa [86] and Gonçalves, Paço [87] showed that 76% and 68%, respectively, of the marine fungi they studied were able to release enzymes related to cellulolytic activity.…”
Section: Release Of Enzymes Hydrolytically Cleaving Carbohydratesmentioning
confidence: 99%